2016
DOI: 10.5367/sear.2016.0293
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Dilemmas, Labour and Remittances: Gender and Intimacies in Cavite, Philippines

Abstract: This paper explores the reproductive dilemmas of individuals from a communal compound in Cavite, which are impacted by the complicated intersection of economic globalization and prescriptions of gendered performances and spatialities. Specifically, it looks at how remittances from overseas Filipino worker (OFW) relatives and the personal desires for overseas mobility directly shape these individuals' decisions regarding reproduction, relationships and intimacies. Wilson's (2004) concept of intimate economies h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The Philippine constitution explicitly argues for the sanctity of the family and enshrines it as the foundational unit of Filipino society. Philippine law also leaves the country as the last one in the world, save for the Vatican, that does not allow for legal divorce (Collantes 2016).…”
Section: Migrant Intimacies In Multicultural Manilamentioning
confidence: 99%
“…The Philippine constitution explicitly argues for the sanctity of the family and enshrines it as the foundational unit of Filipino society. Philippine law also leaves the country as the last one in the world, save for the Vatican, that does not allow for legal divorce (Collantes 2016).…”
Section: Migrant Intimacies In Multicultural Manilamentioning
confidence: 99%
“…Researchers have found that both men and women devalue women's work as temporary, unskilled. and supplementary, even if it represents the main household income (Collantes 2016). Service sector work also relies on and reinforces the care work expected of women; one study showed that tech companies employ strategies such as hiring eldest daughters, whose family responsibilities mean they are less likely to quit or make risky employment demands.…”
Section: Workers Of the Worldmentioning
confidence: 99%
“…This is characteristic not only of the meritocratic society established under the tutelage and ideals of American liberalism but also of a society in which consumption defines status. Consumer culture is materialized in the abundant shopping malls found not only throughout Philippine cities but also beside palenkes, local town markets, or next to fields in which water buffalo graze (Collantes 2016). Malling is something of a national pastime for both urban and rural Filipinos; 80% of Filipinos go to malls at least once or twice a month.…”
Section: Workers Of the Worldmentioning
confidence: 99%